Analysis of Village Fund Fraud Trends in Brebes Regency Government Apparatus - Yusriyanti, Ismi Anggita; Nurcahyono, Nurcahyono (Economics and Business International Conference Proceeding, 2024)
This study aims to determine the influence of information asymmetry, religiosity, organizational culture, and law enforcement on fraud tendencies. This study uses a quantitative approach with a survey method. The population in this study is 23 villages in Brebes District, Brebes Regency, with a total of 103 people. The sampling technique in this study uses probability sampling using simple random sampling where the sample size is determined by the Slovin formula so that 51 people are obtained. The analysis used in this study is a multivariate analysis, namely the application of structural equation modelling (SEM) using WarpPLS 8.0 software. The results of this study show that information asymmetry has a negative effect on fraud tendencies. Meanwhile, religiosity, organizational culture, and law enforcement positively affect fraud tendencies.